The Conundrum of the Article 1087.1 of the Civil Code - Chiflikyan, A. (Bulletin of Yerevan University C: Jurisprudence, 2020)
This study aims to identify the sources and the meaning of certain provisions of article 1087.1. Basically, it is about the 5th section of this article with its three points. The 4th and the 6th sections of this article were also discussed. As a result of the study, it was emphasized that especially the 2nd paragraph of the 5 th section of the article under discussion look borrowed from common law. In particular, the author pointed out that sections 4 and 5 of article 1087.1 are aimed at protecting the interests of the slanderer, thereby guaranteeing the possibility of wider exercise of the right to freedom of speech. Paragraph 2 of section 5 was analyzed in detail, and it was concluded that it refers to the cases of publication of derogatory data that was not made intentionally, but at the same time was intended to serve the Supreme public interest. It was emphasized that reasonable publication allows a person not to bear the negative consequences associated with defamation. In addition, the author’s interpretation of the phrase «conscientiously and carefully present the facts» is given. The author also analyzed the particulars of the presentation of information, which does not constitute libel, about the circumstances of the case by the participant during pre-trial and trial proceedings. Attention was paid to the provision on the burden of proof transfer provided for in section 4 of article 1087.1, showing the subtleties of its application in defamation cases in English law, when the purpose of such transfer is punishing the offender, and in American law, when the victim must be a public person. In addition, the issues of interrelation of sections 5 and 6 of article 1087.1 are analyzed, and parallels are drawn between similar categories provided for in paragraph 3 of section 5 and 6th section.